Detecção de contaminação e a investigação da transmissão vertical do BmNPV (Bombyx mori nucleopolyhedrovirus) em raças do banco de germoplasma de bicho-da-seda da Universidade Estadual de Maringá - Saez, Cláudia Regina das Neves (2012)
In the present work we reported the molecular detection of BmNPV (Bombyx mori nucleopolyhedrovirus) with experimental silkworm breeds of the Universidade Estadual de Maringá germplasm bank. DNA extraction followed routine methodology. DNA of six Bombyx mori females moths of each breed (B82, M11-2, M18, C36, F6, M18-2, M12-2, J1, C25, C75, C24, KR01, M11-A, AS3, B106, M8, M11, C211, E8 and Hindu), composed individual pools gene. PCR (Polymerase Chain Reaction (PCR) used a pair of primers that was designed based on specific sequence of the baculovirus genome corresponding to BmNPV ORF 14. Another pair of primers was used to amplify the silkworm Actin A3 gene segment, which was used as positive control. Twenty gene pools were analyzed, and fifteen showed a band of 443 base pairs, bp, that indicates the presence of BmNPV genome. Populations B82, M11-2, M18, C36 and F6 showed no contamination. The frequency of infected moths of the fifteen gene pools detected as contaminated was investigated by individual PCR amplifications. The frequency of contaminated moths were: 100% for silkworm breeds M18-2, M12-2 and J1, 83% for C25, C75 and C24 breeds, 66% for KR01, 50% for M11-A, 33% for AS3, B106, M8 and M11 and 16% for C211, Hindu and E8 breeds. All DNA amplified by multiplex PCR showed a band of 721 bp, which confirms that the amplified DNA was from B. mori specimens. The detection of PCR fragments of the expected size (443 pb) in infected individuals eggs was not conclusive. The difficulty in detecting BmNPV contamination in eggs may be due the low concentration of virus in samples. These are promising results for the identification of contamination by BmNPV, thus preventing virus proliferation in subsequent generations.